El Sistema Integrado de Administración Financiera Sector Público y su incidencia en la Unidad de Tesorería de la Municipalidad Distrital de San Benito - período 2010. - Horna Cruz, Patricia Liliana (2012)
The Integrated Financial Management System (SIAF SP) is a official tool and mandatory for use in public institutions at national, with the passage of time since it became official in 1999, the system has implemented a series of modules, highlighting the main the MPP (Budgetary Process Module), Accounting Module, Administrative Module, among others. Due to the above the present investigation aims analyze the impact of the Integrated Public Sector Financial Management Treasury Unit in the District Municipality of San Benito, techniques used to gather information from administrative workers involved in the management of the system, through interviews and conversations. The information obtained indicates that the Integrated Financial Management Public Sector although it is weak in the technological infrastructure for presenting inadequate electrical service and the poor internet service, has ordered the administrative management of the Municipality, allowing control and Act compliance by the governing bodies, the procedure of payments through this system ensuring real-time paymaster, provides a global view, transparent and permanent availability of financial resources, provides useful, reliable and consistent for better resource allocation and decision making of the entity.